Neurological soft signs in borderline personality disorder and schizophrenia - Otte, Marie-Luise; Schmitgen, Mike; Wolf, Nadine D.; Kubera, Katharina Maria; Balcik, Yunus; Tech, Chantal; Koc, Mert; Le Prieult, Yéléna; Sambataro, Fabio; Brandt, Geva A.; Fritze, Stefan; Hirjak, Dusan; et al. (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Neurological soft signs (NSS) are subtle sensorimotor abnormalities that have been observed in various mental disorders with neurodevelopmental origin. While NSS have been extensively examined in patients with schizophrenia (SZ), preliminary evidence also suggests that NSS are also present in patients with borderline personality disorder (BPD). However, a transdiagnostic examination of the severity of NSS in BPD compared to SZ is still lacking.
Gesehen am 07.07.2025